Alchemy Project Workshop Report: 'Lessons Learned From Livelihood Interventions In Conflict-Affected Areas' - Jacobsen, Karen (Tufts Archival Research Center, 2005)
A two-day workshop was held from 19-20 February 2004 by the Alchemy Project in Maputo, Mozambique, with implementing partner NGOs from Kenya, Guinea, South Africa, Zambia, Tanzania, Congo (DRC), Burundi and Mozambique. This workshop was organized and coordinated by Alchemy Project Director, Karen Jacobsen, chaired by Angela Raven Roberts (Feinstein International Famine Center), and was hosted by World Relief in Mozambique.